Fitocenozy borów sosnowych na tle zmian klasyfikacji mezotroficznych siedlisk borowych na przykładzie Nadleśnictwa Bolesławiec - Stefańska-Krzaczek, Ewa (Leśne Prace Badawcze, 2012)
We attempt to better explain the connection of vegetation structure and dynamics with changes in the site classification of managed forests in Poland. The paper is focused on forest vegetation in oligotrophic and mesotrophic sites with respect to changes in site classification. The main goal of the paper is to assess the how differences in the vegetation cover of forest sites related to changes in their classification. Three data sets were compared. The first set contained data collected in sites classified in both 1960 and 2004 as oligotrophic fresh coniferous forest (oligotrophic/oligotrophic). The second set contained data collected in mesotrophic fresh mixed coniferous forest sites in 2004, which had been classified as oligotrophic fresh coniferous forest in 1960 (oligotrophic/mesotrophic). The third set contained data collected in sites classified as mesotrophic fresh mixed coniferous forest in both 1960 and 2004 (mesotrophic/mesotrophic). Data were collected from circular plots of 8 m radius in successive stand age-classes. All vascular plants, bryophyte and lichen species were identified and their cover was recorded. In general, mesotrophic sites were richer in vascular plant species and oligotrophic sites were richer in lichen species. The cover of non-tree vascular plants was higher in mesotrophic sites in stand age classes Ia-III, where in oligotrophic sites the cover of lichens was higher. The forest in oligotrophic/mesotrophic sites showed some similarities with oligotrophic/oligotrophic sites, but species composition was more similar to mesotrophic/mesotrophic sites. As a consequence, some indicator species preferred meso- over oligotrophic sites, but probably only at a local scale. However, site re-diagnosis was not connected with forest type changes but rather it relies on the conversion of forest structure, which later causes changes in the spatial heterogeneity of forest communities.